FILM SEBAGAI MEDIA DALAM PEMBELAJARAN SASTRA - Widyahening, Ch. Evy Tri (UNIVERSITAS SLAMET RIYADI, 2014)
Media in teaching learning process is very important, especially in teaching learning literature. One of appropriate media that can be used in teaching learning literature is film. Film can give good contributions in teaching learning literature because it brings educational values, socio-cultural values and morality values. All of those values are very important in developing students' characters. Film has become a part of literary works because it contains of many authors' works and playwrights' works has been perfomed on the big screens and become popular. Â Film can be one of an effective media in improving teaching learning literature such as poetry, drama and prose because it can attract students'attention, it also can motivate them to learn about literary works which are written by the great authors or playwrights then some of those literary works have been filmed. Those films can touch students' sympathy and empathy because literary works show many morality values. Through film as a media in teaching learning literature, students' character can be developed. There are many valuable benefits if we use film as a media in teaching learning process especially in teaching learning process. Key words: media, teaching learning literature, film, educational values, socio-cultural values, morality values, author, and playwright.